2015
DOI: 10.1007/s12015-015-9586-8
|View full text |Cite
|
Sign up to set email alerts
|

Rapid and Efficient Generation of Transgene-Free iPSC from a Small Volume of Cryopreserved Blood

Abstract: Human peripheral blood and umbilical cord blood represent attractive sources of cells for reprogramming to induced pluripotent stem cells (iPSCs). However, to date, most of the blood-derived iPSCs were generated using either integrating methods or starting from T-lymphocytes that have genomic rearrangements thus bearing uncertain consequences when using iPSC-derived lineages for disease modeling and cell therapies. Recently, both peripheral blood and cord blood cells have been reprogrammed into transgene-free … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 24 publications
0
20
0
1
Order By: Relevance
“…These are described in our recent blood reprograming work [30]. In brief, using a density test, we found that re-programing could be achieved with 50 mL of peripheral blood samples, which corresponds to 25,000e30,000 mononuclear cells using a gene integrationefree Sendai virus vector.…”
Section: Why Cb As a Possible Source Of Ipscs?mentioning
confidence: 87%
“…These are described in our recent blood reprograming work [30]. In brief, using a density test, we found that re-programing could be achieved with 50 mL of peripheral blood samples, which corresponds to 25,000e30,000 mononuclear cells using a gene integrationefree Sendai virus vector.…”
Section: Why Cb As a Possible Source Of Ipscs?mentioning
confidence: 87%
“…The capacity of human iPSCs to retain patient-specific genomic, transcriptomic, proteomic, metabolomic, and other visualized big data information makes it possible to extend their applications beyond disease modelling into the field of personalized medicine which encompasses the adoption of novel prevention and treatment strategies based on individual variability [65]. The emergence of modern iPSC technology, with the capacity of these stem cells to undergo unlimited self-renewal and differentiation into any type of cell, has a great potential to advance translational applications including stem cell therapies and the generation of large-scale collections of cell lines for research purposes [67]. Recently, genomic editing technologies have been applied to correct the mutations in disease-specific iPSCs to create gene-corrected iPSCs that can be utilized in autologous stem cell-based therapies [64].…”
Section: Ipscsmentioning
confidence: 99%
“…These iPSCs were, in turn, successfully differentiated to GABAergic neurons [18]. Moreover, recent studies demonstrate the successful derivation of iPSCs from PBMCs collected from Alzheimer disease (AD) and Parkinson disease (PD) patients [20-25]. Undeniably, blood is becoming a routinely used source for iPSC generation.…”
Section: Peripheral Blood Mononuclear Cells (Pbmcs) As Source For Ipsmentioning
confidence: 99%
“…Furthermore, in our experience, reprogramming success is not adversely affected when performed on PBMCs extracted from aged patients, in clear contrast with dermal fibroblasts extracted from elderly patients. In support of this convenient source of iPSCs we, as well as other laboratories, have successfully demonstrated the feasibility of using this accessible resource for cell reprogramming and modeling diseases like ASD, AD and PD [3,20-25]. …”
Section: Benefits Of Pbmcs As a Source For Ipsc Derivationmentioning
confidence: 99%